Administrative and legal aspects of hydraulic engineering (selected issues) - Kucharski, Krzysztof (Polish Yearbook of Environmental Law, 2020)
The subject of analysis in the article are selected administrative and legal issues of hydraulic engineering. These problems occur in particular with reference to the Building Law Act, as it constitutes the fundamental regulation in the construction process. The specificity of regulation of the construction of water equipment contained in the Water Law Act has also been indicated. An evaluation of the solutions adopted in the Water Law has been carried out.